2011
DOI: 10.1073/pnas.1104922108
|View full text |Cite
|
Sign up to set email alerts
|

Five phosphonate operon gene products as components of a multi-subunit complex of the carbon-phosphorus lyase pathway

Abstract: Organophosphonate utilization by Escherichia coli requires the 14 cistrons of the phnCDEFGHIJKLMNOP operon, of which the carbon-phosphorus lyase has been postulated to consist of the seven polypeptides specified by phnG to phnM . A 5,660-bp DNA fragment encompassing phnGHIJKLM is cloned, followed by expression in E. coli and purification of Phn-polypeptides. PhnG, PhnH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 27 publications
4
65
0
Order By: Relevance
“…Additionally, these data are consistent with results obtained Ͼ2 decades ago by Frost and coworkers, who demonstrated that C-P bond cleavage by C-P lyase occurs by a radical reaction mechanism (44)(45)(46). Also, amino acid sequence alignments of Phn polypeptides revealed a remarkable evolutionary conservation of PhnJ compared to other Phn polypeptides, consistent with the critical enzymatic function of PhnJ (40,47). The 2-hydroxyl of the phosphoribosyl moiety plays a crucial role in C-P lyase catalysis, possibly in turning over a covalent PhnJ-phosphoribosyl intermediate.…”
Section: Mesorhizobium Lotisupporting
confidence: 80%
See 2 more Smart Citations
“…Additionally, these data are consistent with results obtained Ͼ2 decades ago by Frost and coworkers, who demonstrated that C-P bond cleavage by C-P lyase occurs by a radical reaction mechanism (44)(45)(46). Also, amino acid sequence alignments of Phn polypeptides revealed a remarkable evolutionary conservation of PhnJ compared to other Phn polypeptides, consistent with the critical enzymatic function of PhnJ (40,47). The 2-hydroxyl of the phosphoribosyl moiety plays a crucial role in C-P lyase catalysis, possibly in turning over a covalent PhnJ-phosphoribosyl intermediate.…”
Section: Mesorhizobium Lotisupporting
confidence: 80%
“…which may cause the coupling of transport and catabolism of phosphonic acids (40). Additionally, the phnGHIJK cistrons, i.e., the cistrons encoding the PhnGHIJK protein complex, show translational coupling.…”
Section: The Phosphonate Proteome and Transport Metabolonmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphonate-binding and -uptake proteins have not previously been described as playing a role in biofilm formation. In E. coli, phosphonates are taken into the cell and converted to phosphates, likely to meet nutritional requirements (30)(31)(32)(33). It is not known if PhnD has an analogous role in S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
“…The phnCDEFGHIJKLMNOP operon encodes 14 proteins essential for growth on phosphonates such as MePn: PhnE is the permease subunit in the PhnCDE ABC transporter, and PhnGHIJK form the complex essential for cleaving the C-P bond in phosphonates (15,26,35). We confirmed that the evolved strain ENZ1901 (phnE ϩ ) grew with the same efficiency on MePn or P i as the sole source of P, whereas the ancestral strain ENZ535 (phnE::8 bp) did not grow on MePn but gave rise to variants at a high frequency of Ϸ2 MePn ϩ cells per 10 5 total cells (data not shown), compared with a typical frequency of Ϸ10 Ϫ7 for a singlebase substitution (10).…”
Section: Figmentioning
confidence: 99%